THE FACTORS AFFECTING COMMUNICATION COMPETENCY OF DENTAL HYGIENE STUDENTS - Lim, Soon (International Journal of Engineering Technologies and Management Research, 2017)
The purpose of this study is to understand factors affecting on communication competency in dental hygiene students. From September 20 to October 20, 2016, 439 students participated in survey through structured questionnaire. The results showed that mean of communication competency was 3.46±0.41 and mean of communication apprehension was 3.26±0.59, speech apprehension was highest in sub-factors of communication apprehension. The group of intention to receive communication education and the group of interpersonal satisfaction showed high communication competency and self-efficacy, low communication apprehension. But differences of communication competency according to communication education experience was not statistically significant. A negative correlation was found between communication competency and communication apprehension, self-efficacy and communication apprehension. A positive correlation was observed between communication competency and self-efficacy. The higher self-efficacy and the satisfaction with interpersonal relation, the higher communication competency is. In conclusion, to increase communication competency of dental hygiene students it needs efforts to improve self-efficacy and satisfied interpersonal relationship as well as communication skill education.